Efficient experimental characterisation of the permeability of fibrous textiles. (December 2016) - Swery, Elinor E; Allen, Tom; Comas-Cardona, Sebastien; Govignon, Quentin; Hickey, Chris; Timms, Jamie; Tournier, Loic; Walbran, Andrew; Kelly, Piaras; Bickerton, Simon
Two experimental set-ups used to characterise the in-plane and through-thickness permeabilities of reinforcing textiles have been developed and are presented. Both the experimental testing and data processing techniques used have been selected to ensure that the characterisation is completed in an efficient and robust method, increasing the repeatability of tests while minimising user induced errors as well as the time and resources needed. A number of key results and outputs obtained are presented from tests carried out on a plain woven reinforcing textile with a range of number of layers and at different fibre volume fractions.